Iodine-catalyzed Synthesis, Antibacterial, and Antioxidant Activity of Isatin Derivatives - Antonius Herry Cahyana; Agus Rimus Liandi; Yosua Ongkowidjawa (Universitas Gadjah Mada, 2024)
Isatin is a unique compound with many bioactivities such as antiviral, anti-HIV, antitumor, anti-inflammatory, anticonvulsant, and antifungal. In this study, isatin derivatives were synthesized with an iodine catalyst and tested for antibacterial and antioxidant activities. Isatin derivatives were conducted through a Knoevenagel condensation reaction between isatin and malononitrile. The products were confirmed by thin-layer chromatography, melting point apparatus, FTIR, UV-vis spectroscopy, and LC-MS. The optimum reaction conditions were obtained at 10% mol of catalyst, at boiling point ethanol solvent for 30 min. The yield of the isatin derivative products was 71% (3a), 61% (3b), and 67% (3c). The antibacterial activities of the synthesized compounds were weak activity against S. aureus and E. coli. The antioxidant activity test resulted in IC50 values of 266.47, 220.43, and 654.85 ppm for compounds 3a, 3b, and 3c, respectively. The synthesis method using an iodine catalyst in this reaction offers a higher product yield compared to a catalyst-free reaction.